Social workers and general practitioners—some problems of working together - Ratoff, L. (1974)
Generally, relations between general practitioners and social workers are poor. Differences in approach, role perception, working situations and the organisation and staffing of the two professions may create difficulties. Conflicts of statutory roles, authority and accountability, record keeping, and confidentiality all produce problems. Finally unrecognised attitudes may also interfere with good co-operation. We hope to stimulate vigorous discussion of these important issues by members of both professions.